PROSEDUR PEMBAYARAN UTANG USAHA DI PERCETAKAN PT GRAMEDIA, JAKARTA - Maria Dyah Rahayu (2023)
All small and large companies have debt in the companies they form. Therefore, it is necessary to make procedures to be able to manage finances in a company. Debt will arise due to past events and must be paid immediately in the future. In this case, debt has two classifications, namely short-term and long-term debt. short-term debt must be paid off within 45 days or 60 days according to the agreement, while long-term debt can be paid off in less than twelve months. The procedure carried out by the company in paying debts is ordering goods from suppliers, receiving goods, approving invoices from suppliers, and finally paying debts. Documents related to debt payment procedures are invoice, delivery order,purchase order, and tax invoice. This document is support for debt payment procedures which will be archived as company records.